PENYULUHAN TENTANG INDONESIAN HERBS FOR HEALTHY DRINKS DAN PELATIHAN PEMBUATAN MINUMAN HERBAL SEBAGAI PENINGKATAN IMUN TUBUH: Counseling About Indonesian Herbs for Healthy Drinks And Training Herbal Drinks Production As Immune Enhancements - Ferika Indrasari; Metrikana Novembrina; Eleonora Maryeta Toyo; Rizky Adian Hartanto Syawal; Wahyu Setyaningsih (Forind Press, 2023)
Herbal drinks are drinks that come from natural ingredients that are beneficial to the body. Herbal drinks are made from natural spices or parts of plants, such as roots, stems, leaves, flowers, or tubers which are believed to have properties to increase the body's immune system. Purpose: to provide counseling and manufacture herbal drinks as an immune booster. Method: measurement of initial and final knowledge by completing questionnaires, for counseling, is carried out by lectures/presentations, discussions, and questions and answers. Processing and analysis of data using testT-Test. Result: the counseling has gone according to plan and succeeded well. Evaluation results before (pretest) and after counseling (post-test), it can be seen that the significance value is 0.000 (<0.05). This shows that there is an increase in knowledge for respondents after counseling activities are held.